Ethnochemistry of Kampung Naga: Local Wisdom as Green Chemistry Learning in E-Book Form - Natania, Alya; Subarkah, Cucu Zenab; Sundari, Citra Deliana Dewi (Chemistry Education Department of Education and Teaching Faculty, 2025)
This study explores the local wisdom of Kampung Naga as a source of ethnochemistry-based green chemistry learning through an e-book. The research focuses on forest conservation, waste management, natural architecture, water systems, and traditional agricultural and food practices. This study employed a descriptive qualitative approach using an ethnographic method to explore the local wisdom of the Kampung Naga community in relation to ethnochemistry and green chemistry concepts The research target were members of the Kampung Naga community selected through purposive sampling. Data were collected through observation, interviews, questionnaires, and documentation, and analyzed descriptively. The findings show that local wisdom of Kampung Naga encompasses ethnochemical practices that are relevant to chemical concepts. These practices align with the principles of green chemistry, particularly in waste reduction, the use of renewable materials, and energy efficiency. Although challenges remain, such as the open burning of plastic, which poses pollution risks the community's approach to maintaining harmony with nature offers a strong framework for developing chemistry education based on ethnoscience.